TINJAUAN KARAKTERISTIK GURU GAMBAR TEKNIK YANG DISENANGI SISWA PROGRAM STUDI TEKNIK BANGUNANSMK NEGERI 2 SOLOK - 1103-1118 , Elfia Fatri Yeni (CIVED, 2016)
ABSTRACTThis research is a descriptive quantitative research. The research population was all students of class XI and XII Building Engineering Program with a number of 137 people. Samples of this research consisted of 58 people with sampling techniques using proportionate random sampling. This study has only one variable that is characteristic of Master Image of favored teacher by students. The research data collection tool was a questionnaire using a Likert scale to measure each statement. Results of this research indicate that a review of the technical drawing teacher characteristics favored by students seen from indicators of intelligence, the highest percentage of indicators of intelligence is as much as 96.56% of the students said he/she was happy with the technical drawing teacher who possess intellectual, the highest percentage of professional indicators as many as 96 , 56% of students declare happy with teacher drawing techniques to master the material, the highest percentage indicator of expertise is as much as 100% of the students said he/she was happy with the teachers who understand the drawings of building materials, and the highest percentage indicator of personality that is as much as 96.56% of the students happy with teacher  who friendly and can be a good example. Keywords: Karakteristik, Gambar Teknik, Disenangi